Discovery Learning Assisted by Animation Audio Visual Media Optimizes Problem Solving Ability and Students' Independent Attitude - Niken Ayu Mutiasari; Rusnilawati (Jurnal Ilmiah Sekolah Dasar, 2022)
Monotone learning activities make students easily bored and not interested in learning. Such a learning process cannot train students to think critically and cannot be digested optimally by students. This study aims to analyze the discovery learning model assisted by audio-visual animation media to optimize problem-solving abilities and student independence attitudes. This type of research is quantitative research. This study uses a quantitative approach with experimental methods. The population in this study were all third-grade students at SDN Cengklik Surakarta, amounting to 64 students. Data collection techniques were obtained through the test and the non-test. The data analysis technique is descriptive qualitative, quantitative, and statistical inferential analysis. The results showed that using the Discovery learning model assisted by audio-visual animation media affected students' ability to solve learning problems and fostered student independence. It was concluded that the Discovery learning model assisted by audio-visual animation media could improve students' ability to solve learning problems and foster student independence.